2018
DOI: 10.1096/fj.201800221r
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate (S1P) induces potent anti‐inflammatory effectsin vitroandin vivoby S1P receptor 4‐mediated suppression of 5‐lipoxygenase activity

Abstract: Sphingosine-1-phosphate (S1P) is involved in the regulation of important cellular processes, including immune-cell trafficking and proliferation. Altered S1P signaling is strongly associated with inflammation, cancer progression, and atherosclerosis; however, the mechanisms underlying its (patho)physiologic effects are only partially understood. This study evaluated the effects of S1P in vitro and in vivo on the biosynthesis of leukotrienes (LTs), which form a class of lipid mediators involved in the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Comparing the predicted affinities towards S1P 1 and S1P 3 receptors showed excellent selectivity for compound 452 (S1P 3 EC 50 /S1P 1 EC 50 : 13489). This level of predicted selectivity is comparable with the selectivities reported for S1P 1 agonists in clinical trials such as ozanimod [19] and siponimod [40] and much greater than that of compound 61, indicating that compound 452 is noteworthy to be evaluated in experiments for development of a potent and selective S1P 1 agonist. Moreover, among the selected compounds, compound 799 showed high predicted EC 50 value (0.68 nM) with acceptable S1P 1 over S1P 3 selectivity (5888 times), demonstrating its feasibility to be explored as a potent and selective S1P 1 agonist.…”
Section: Identification Of Selective S1p 1 Receptor Agonist Candidatessupporting
confidence: 78%
“…Comparing the predicted affinities towards S1P 1 and S1P 3 receptors showed excellent selectivity for compound 452 (S1P 3 EC 50 /S1P 1 EC 50 : 13489). This level of predicted selectivity is comparable with the selectivities reported for S1P 1 agonists in clinical trials such as ozanimod [19] and siponimod [40] and much greater than that of compound 61, indicating that compound 452 is noteworthy to be evaluated in experiments for development of a potent and selective S1P 1 agonist. Moreover, among the selected compounds, compound 799 showed high predicted EC 50 value (0.68 nM) with acceptable S1P 1 over S1P 3 selectivity (5888 times), demonstrating its feasibility to be explored as a potent and selective S1P 1 agonist.…”
Section: Identification Of Selective S1p 1 Receptor Agonist Candidatessupporting
confidence: 78%
“…S1P is a bioactive lipid, primarily carried by apoM on HDL, and signals its G protein-coupled receptors, named S1PR1-5 [5], S1P is degraded by two pathways: dephosphorylation by S1P phosphatases (SPP1/2) and irreversible cleavage by S1P lyase (SPL). S1P has dual nature in the pathogenesis of atherosclerosis: S1P preserves endothelium via S1PR1/3 [121]; inhibits smooth muscle cells migration via S1PR2; and possesses anti-inflammatory properties via S1PR4 [122]; while S1P also promotes inflammatory monocyte/macrophage recruitment through S1PR2/3 [123,124]. Although it is yet not concensus, several clinical data reported that plasma S1P concentrations were negatively associated with prevalence and severity of CAD and myocardial infarction [125–130].…”
Section: S1p and Atherosclerosismentioning
confidence: 99%
“…Thus, there is an urgent need to establish an efficient and reliable assay to quantify the S1P. At present, there is a lack of data on the relationship between the influencing factors of tumor treatment and monitoring results of S1P concentration . Previous studies have focused on the establishment of a certain method and did not apply it to the treatment and differences in specific cancer patients.…”
Section: Discussionmentioning
confidence: 99%